BLENDED ONLINE LEARNING CULTURE IN AN INDONESIAN TERTIARY EDUCATION DURING COVID-19 PANDEMIC - Mu'ayyadah, Kholishotul; Sahiruddin, Sahiruddin (Studi Budaya Nusantara, 2020)
The COVID-19 outbreak caused all schools and tertiary educations to be closed. Based on the government's regulation that all teaching and learning activities should be carried out from home through online platform to reduce the expansion of the COVID-19 outbreak. This pandemic situation has changed learning culture in general (Kim, 2020). This condition also encourages lecturers to apply the blended online learning (BOL) method during a pandemic. This present study explores the effect of implementing the blended online learning during pandemic on the development of English language skills, students' perception concerning benefits, limitations, and suggestion of implementing the blended online learning during pandemic. This research used quantitative method for the data collection by using online questionnaire containing 34 Likert-scale and three open-ended questions. The participants were 86 students in an Indonesian tertiary education. The data were analyzed using SPSS 22 to know the reliability, mean and standard deviation of the data. The result revealed that the development of listening, reading and vocabularies skills were mainly affected by implementation of blended online learning during pandemic. The students also perceived that they could develop internet and computer skill and self-paced learning. Moreover, the major problems of implementing the blended online learning included connectivity, followed by preference for hard books than online material. Pedagogical implication includes the need for students to be familiarized with solving technical problems and providing proper online learning training associated with how to learn effectively at blended online learning.